O show tem que continuar: propostas de mensuração do valor cultural e econômico dos palcos de pequeno e médio porte na cidade do Rio de Janeiro - Guarisa, Maria Luísa Zarur (2021)
The segment of private grassroots music venues had already been going through a crisis in their business model in recent years. However, their difficulties increased due to the impacts of the COVID-19 pandemic and the scenario of a hyperconsumption society, which manifests in the music industry through the extreme concentration of the market in few artists and in large festivals or concerts immersed in the concept of experience. Therefore, this work proposes ways to measure the cultural and economic value of private grassroots music venues in the city of Rio de Janeiro, seeking to highlight the important role of such venues and of public and private support for their maintenance and continuous operation. To achieve this goal, in-depth qualitative interviews were conducted with six managers of these venues, seven artists and a public agent as a way to identify their cultural value and broaden the debate on their operating characteristics and difficulties faced. Then, an online survey of quantitative nature was applied, based on the contingent valuation method, with 180 grassroots music venues goers and 188 non-goers. This section seeks to demonstrate the economic value of these venues, as well as their non-use value for the population of Rio de Janeiro. Based on the collected data, it is identified that grassroots music venues play an important role within the musical ecosystem and generate positive externalities for Rio de Janeiro. Furthermore, both its goers and non-goers tend to understand this importance and identify that they are businesses that generate cultural and economic value for the city. Nevertheless, they need the support and recognition of public and private sectors and also lack a management with technical skills, as a way to soften certain difficulties. This work can be applied, in a practical way, as a material for grassroots music venues owners in the city to rethink management strategies, as well as a basis for advancing the debate with public authorities and private organizations, presenting the positive externalities that come from these establishments